The Development of Coronavirus Anxiety Scale in Urdu (CASU) - Hussain, Sadiq; Ahmad, Sabih (Journal of Pakistan Psychiatric Society, 2021)
Objective: We aimed at developing an instrument to screen anxiety symptoms related to Covid-19, in Urdu language. Design: A descriptive study. Place & Duration: Combined Military Hospital, Kharian Cantonment, Pakistan, from September to December 2020. Methods: A six step approach was taken up for development of the scale. A pilot study was conducted on the final scale, followed by a validation study involving 400 gender balanced volunteers. Exploratory factor analysis was performed using Varimax rotation, which identified a uni-dimensional model. Confirmatory factor analysis was performed using goodness of fit model, standardized root mean square residual, root mean square error of approximation, comparative fit and Tucker-Lewis indices. Scoring of the scale was Likert – type. Results: Fulfilling the prerequisites was followed by factor analysis. Uni-dimensionality with acceptable range of variance was established. Confirmatory factor analysis was performed, and the goodness of fit indices indicated that our model fitted the data well. Crohnbach’s alpha was 0.75, Spearman Brown coefficient was 0.68, and Guttmann split-half coefficient was 0.69. Different demographic variables were found to influence the anxiety levels, like age and level of education. Conclusion: CASU was found to be a reliable and valid self-administered instrument to screen people with Covid-19 related anxiety.